An Exploratory Study of the Differences in Attitudes and Motives Regarding COVID-19 Plasma Donation - Maheshwari, Ashish; Varshney, Mohit; Bajpai, Meenu; Raizada, Neeraj; Sharma, Tarika (Acta medica Lituanica, 2022)
Background: Understanding the attitude and motives and differences between voluntary and replacement blood donation is the key to the sustainable availability of this precious resource. This study aimed to assess the attitude and motives for convalescent plasma (CP) donation in the recovered COVID-19 plasma donors and further understand the differences between voluntary and replacement donation.Materials and Methods: This prospective cross-sectional survey-based study was conducted among500 COVID-19 recovered blood donors who visited for CP donation at a tertiary care super-speciality centre in northern India. Data were collected using a structured questionnaire based on donor attitude, motives, and belief, which was validated by the experts of Psychiatry, Transfusion Medicine, and Epidemiology and was administered by the online medium.Results: The study’s findings depicted that voluntary plasma donors were previously regular blood donors (36.8%) compared to replacement plasma donors (26.4%). Almost all voluntary donors (99.5%) showed altruistic reasons to donate plasma and expressed that donating plasma is a good way to save a life, and it was more than for replacement plasma donors (p=0.004). The motives of most voluntary plasma donors were to contribute to society, and they believed that donating plasma is a good way, while it was not the case for most replacement plasma donors (p=0.02). Voluntary donors were more eagerly willing to donate plasma to help COVID sufferers (40.9%) when compared to replacement donors (33.2%) (p=0.037).Conclusion: Most voluntary plasma donors were regular whole blood donors and were keen to contribute to society. Convalescent plasma donation during this time of grief and loss was considered a moral responsibility by voluntary donors. The impact of media was more highly perceived in voluntary plasma donors when compared to replacement donors.
Keywords: plasma donors; plasma donation; attitudes; motives